Virtual integration in SMEs : The digitalization circuitry of dynamic strategic planning for SMEs - Ojha, Divesh; Patel, Pankaj C.; Parida, Vinit (Elsevier, 2023)
Though digital technology adoption among SMEs is widely studied, a manifestation of digitalization – virtual integration, particularly its strategic benefits for SMEs – remains largely understudied. Virtual integration connects and coalesces the interfaces of digitalization in SMEs. Though the need for externally oriented digitalization in SMEs is widely desired and espoused, virtual integration and the ensuing effect on Dynamic Strategic Planning (DSP) could be key factors in realizing higher performance. Using the information theory lens and knowledge-based view and a two-study empirical setup based on data from manufacturing and services firms, we draw on the Competence–Capability–Performance (CCP) framework. Specifically, we test a model of digitalization circuitry operational through the mediating effects of virtual integration and dynamic strategic planning (DSP). The ensuing interweaving effects of digitalization from virtual integration are manifest in DSP through fluid partnering, business continuity planning, and market acuity. We find that digitalization, manifested in the form of virtual integration, cascades through DSP to improve financial performance.
Keywords: Virtual integration; Dynamic capabilities; Competencies; DSP; fi=Strateginen johtaminen|en=Strategic Management|